The Influence of Leadership and Working Environment on Employee Performance with Work Motivation as Intervening Variable: The Case of PT Sawit Mas Sejahtera Kabupaten Lahat - Ariyanti, Nopen; Rahayu, Sri; Yamani, M. Fadhil (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research aims to determine the influence of leadership and work environment on employee performance with work motivation as an intervening variable at PT Sawit Mas Sejahtera, Lahat Regency. The type of research is associative. Leadership, work environment, motivation, and performance are the variables used. The research sample consisted of 200 PT Sawit Mas Sejahtera employees, Lahat Regency, who were selected using cluster sampling. The data used is primary data with a questionnaire data collection method. Structural Equation Modeling (SEM) with the Lisrel application program is the data analysis technique. The research results show that (1) leadership has a positive and significant effect on employee work motivation, (2) the work environment has a positive and significant effect on employee work motivation, (3) leadership has a positive and significant effect on employee performance, (4) the work environment has an effect not significant on employee performance, (5) work motivation has a positive and significant effect on employee performance of PT Sawit Mas Sejahtera Lahat Regency.